Studies of Lateral Interactions Between C18 Unsaturated Fatty Acid with Polyethoxylated Phospholipid Mixed Langmuir Monolayer at Air-Aqueous Interface for Liposome Formulation - Teo, Y.Y.; Misran, M.; Low, K.H. (Asian Journal of Chemistry, 2014)
Intermolecular interactions between C18 polyunsaturated fatty acid and polyethoxylated phospholipids have been studied by surface pressure-area isotherm. The effect of fatty acids' unsaturation degree and polyethoxylated phospholipids with different molecular weight namely, 1,2-dipalmitoyl-sn-glycerol-3-phosphoethanolamine-N-[methoxy-(polyethylene glycol)-2000] (DPPE-PEG2000) and 1,2-dipalmitoyl-sn-glycerol-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-5000] (DPPE-PEG5000) on the stability of monolayer have been investigated. The obtained isotherms were analyzed quantitatively to evaluate the thermodynamic properties such as miscibility, compression modulus and stability of the mixed monolayer on phosphate buffer subphase. We found that miscibility for mixture of oleic acid and DPPE-PEG5000 is limited to higher mole fraction of DPPE-PEG5000. Whereas DPPE-PEG2000 is more compatible with oleic acid and DPPE-PEG5000 is more compatible with linoleic acid. These findings provide valuable information for the preparation of PEGylated fatty acid liposome and understanding on the interaction between fatty acid and polyethoxylated phospholipid in the lipid bilayer membrane as well as their membrane stability.